2019
DOI: 10.1016/j.apacoust.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Gear transmission rattle: Assessment of meshing forces under hydrodynamic lubrication

Abstract: Noname manuscript No.(will be inserted by the editor) GEAR TRANSMISSION RATTLE: ASSESSMENT OF MESHING FORCES UNDER HYDRODYNAMIC LUBRICATIONA. Fernandez-Del-Rincon · A. Diez-Ibarbia · S. TheodossiadesReceived: date / Accepted: date Abstract The dynamic behavior of gear transmissions poses several challenges from the standpoint of design and requires the availability of more advanced models capable of simulating a wide range of operating conditions. In this paper, several formulations to represent efforts relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 27 publications
(32 reference statements)
1
9
0
Order By: Relevance
“…Within this framework, the lubricant role is still to be understood, specifically under non-stationary conditions, since only few studies deal with this issue [1,6,7,26,27,28], being this the main goal of the present work, as well as the novelty with respect to the preliminary hydrodynamic force analysis under gear rattle conditions performed in [11]. In this regard, in previous analysis of the authors [11], six hydrodynamic formulations found in literature [29,30,31,32], which consider both squeeze and entraining fluid effects to model the fluid contact in HDL conditions, were implemented in the model developed by the authors [9,12,13] to simulate gear rattle under stationary conditions. Specifically, several mean input velocities were considered in that analysis, obtaining the dynamic response under several torque cases, concluding that, when constant input speed was considered, the wedge term overcomes the squeeze term effect on the dynamic response.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Within this framework, the lubricant role is still to be understood, specifically under non-stationary conditions, since only few studies deal with this issue [1,6,7,26,27,28], being this the main goal of the present work, as well as the novelty with respect to the preliminary hydrodynamic force analysis under gear rattle conditions performed in [11]. In this regard, in previous analysis of the authors [11], six hydrodynamic formulations found in literature [29,30,31,32], which consider both squeeze and entraining fluid effects to model the fluid contact in HDL conditions, were implemented in the model developed by the authors [9,12,13] to simulate gear rattle under stationary conditions. Specifically, several mean input velocities were considered in that analysis, obtaining the dynamic response under several torque cases, concluding that, when constant input speed was considered, the wedge term overcomes the squeeze term effect on the dynamic response.…”
mentioning
confidence: 99%
“…In order to avoid repetitions with the aforementioned analysis [10,11], only a summary of the lubrication concepts and the dynamic model is described in sections 2 and 3, highlighting the required information for this specific study. Then, the tests set-up and results are discussed in sections 4 and 5 whilst the conclusions are exposed in section 6.…”
mentioning
confidence: 99%
“…Spur gear has been extensively implemented in vehicles, ships, aviation and other fields with its advantages of accurate and stable transmission and high efficiency (Dai et al, 2021;Liu et al, 2020;Mo et al, 2019Mo et al, , 2020a. The state of the tooth surface is one of the key factors that determine lubrication characteristics, load capacity and service life of the gear (Fernandez-Del-Rincon et al, 2019;Lorenz et al, 2021;Simon, 2019;Wang and Zhu, 2021). Generally, gear tooth surface roughness is of the same order of magnitude as the minimum film thickness.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature reviewed, there are two kinds of noise emitted from the automotive gearbox, namely, gear rattle noise and gear whine noise. Gear rattle noise is generally caused by fluctuations in the engine torque and speed [1][2][3][4], which usually lead to contact loss and impacts between lightly loaded mating gears. Gear rattle noise also has a close relationship with lubricant conditions [5][6][7].…”
Section: Introductionmentioning
confidence: 99%